Internet Violence: Perceptions and Experiences of Activists Working on Sexuality and Sexual Rights - Schenone Sienra, Delfina (2019)
This study focuses on finding out how activists working on gender, sexuality and sexual rights that use internet as a mean of expression and activism, experience situations of surveillance, censorship and online harassment. Data gathering and analysis were both quantitative and qualitative. The information was gathered with an online survey and with in-depth interviews. The sample includes activists from Latin America and the Caribbean,South, South East and East Asia, Africa, North America and Western Europe, West Asia and Eastern Europe.Our study centres on the discussion of feminist perspectives that problematize the use of the internet, where we maintain that while the internet allows for enhanced visibility and communication among activists, it is also a space for violence such as censorship, discrimination, surveillance and harassment, primarily in the form of harassment, intimidating comments and the blocking of webpages, or the use of software filtering that prevents users from accessing information. We analyse these topics taking into account how gender identity, sexual orientation, regions and work-related issues in sex rights activism are involved in the aforementioned actions taken against activists. In addition, we explore the different actors that, according to activists, are responsible for the violence they suffer.